2020
DOI: 10.1093/jmcb/mjaa011
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of tumor suppressive ASXL1−PTEN/AKT axis in myeloid malignancies

Abstract: Mutations of epigenetic regulators are pervasive in human tumors. ASXL1 is frequently mutated in myeloid malignancies. We previously found that ASXL1 forms together with BAP1 a complex that can deubiquitinylate mono-ubiquitinylated lysine 119 on Histone H2A (H2AK119ub1), a Polycomb repressive mark. However, a complete mechanistic understanding of ASXL1 in transcriptional regulation and tumor suppression remains to be defined. Here we find that depletion of Asxl1 confers murine 32D cells to IL3-independent grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Thus, these findings revealed a function of ASXL1-MT as a signaling modulator beyond its known roles as an epigenetic regulator. On the other hand, one recent study has shown that Asxl1 loss activates Akt/mTOR pathway due to an epigenetic dysregulation at the Pten locus 65 . Thus, we cannot completely exclude the possibility that ASXL1-MT activates Akt/mTOR pathway through an epigenetic-dependent manner as well.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these findings revealed a function of ASXL1-MT as a signaling modulator beyond its known roles as an epigenetic regulator. On the other hand, one recent study has shown that Asxl1 loss activates Akt/mTOR pathway due to an epigenetic dysregulation at the Pten locus 65 . Thus, we cannot completely exclude the possibility that ASXL1-MT activates Akt/mTOR pathway through an epigenetic-dependent manner as well.…”
Section: Discussionmentioning
confidence: 99%
“…And we have demonstrated that ASXL1 is driven to erase H2AK119ub1 for transcription induction. Loss of ASXL1 leads to the retention of H2AK119ub1 at the regulatory loci of INK4B and PTEN and thereby the inactivation of these two well-known tumor suppressor genes in response to oncogenic signals, supporting ASXL1 as a tumor suppressor ( Wu et al, 2015 ; Cao et al, 2020 ).…”
Section: Mechanistic Insights Into H2ak119ub1 Deregulation In Malignamentioning
confidence: 99%
“…Similarly, PI3K p110δ isoform level followed the same pattern of association in myeloblasts of progressing MDS patients [ 30 ]. Another paper recently showed that ASXL1 mutations, which are often associated with lower PTEN levels, exhibit significantly higher sensitivity to the AKT inhibitor MK2206, consistent with the fact that excessive PI3K/AKT/mTOR activation may be a direct consequence of HMAs targeting the general mechanism of transcriptional repression (hence protection of chromatin structure) as well as AML cell survival [ 31 ].…”
Section: Discussionmentioning
confidence: 78%
“…This signaling pathway is often dysregulated in resistant cells to various antileukemic agents [ 32 ]. However, the use of SOR in AML patients is quite effective, especially in patients with FLT3-ITD mutation [ 33 ], leading to prolonged survival [ 31 ], again reinforcing the importance of the RAS/RAF/MEK/ERK signaling pathway. Regarding signaling through a family of different Src kinases (including LYN and SRC), these are expressed in AML and their phosphorylation regulates leukemia cell proliferation and survival (including through LYN mediating mTOR activation) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%